PEMBUATAN MEMBRAN SELULOSA ASETAT DARI TANDAN KOSONG KELAPA SAWIT TERMODIFIKASI MIKRO ZEOLIT ALAM UNTUK FILTRASI AIR SUNGAI - Pada Mulia Raja (Institut Teknologi Sawit Indonesia, 2017)
The aim ofthis research is to studypreparation cellulose acetate membranesfrom palmfruit empty bunch by additing natural zeolite sarulla for filtration of river water. This study consists of several stages: Preparation cellulose acetate from palm fruit empety bunch, Preparation cellulose acetate membranes from palm fruit empety bunch by additing natural zeolite and analysis ofriver water parameters include TDS, TSS, turbidity, pH and Metal Fe. Composition of cellulose acetate membranes used were 15% w/v cellulose acetate, acetone, mikrozeolit 0%; 5%; 10%; 15%; 20%; 25% and30% (w/v). River water before filtration with cellulose acetate membrane has TDS 60 mg/L, TSS 35 mg/L, turbidity 10 NTU, pH 6,56, andFe is 0,86 mg/L. Afterfiltration with a cellulose acetate membrane and cellulose acetate membrane with the addition ofzeolite Has optimum decreased TDS12 mg/L, TSS 15 mg/L, turbidity 2 NTU, pH 6.5 andFe 0.55 mg/L and zeolite interaction with dissolved solids (suspensed) is the interaction ofphysical adsorption.